Usury in Online Loans and Pay Later: From Historical Perspective to Its Contextualization on Modern Practice - Nurrohim, Ahmad Hujaj; Abdurrahman, Landy Trisna; Imam, Khairul (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
Abstract: The enthusiasm of the Muslim community in Indonesia for various fintech products, especially Peer-to-Peer Lending (Online Loans and Pay Later), remains substantial. Non-Sharia-based Online Loans and Pay Later have been deemed haram (forbidden) by MUI, while the availability of Sharia-compliant services in Online Loans and Pay Later is limited. Fatwas regarding online loans and Pay Later refer to the prohibition of usury due to the presence of